Returns to Education in Professional Football - René Böheim; Mario Lackner (Johannes Kepler University of Linz, Department of Economics, 2011)
After three years in the National Collegiate Athletic Association (NCAA), collegiate football players face a trade-off between spending more time in the NCAA and pursuing a career in the National Football League (NFL) by declaring for the draft. We analyze the starting salaries and signing bonuses for 1,673 rookies in the NFL, who entered the league between 2001 and 2009 through the NFL draft. We instrument the endogenous decision to enter the professional market with a player's month of birth. A player's true talent is only imperfectly observed and the instrument pro- vides a causal link between time at college and subsequent salaries in the NFL through the relative age effect. Our estimates suggest that a player enjoys a 6% higher starting salary in the NFL, and a 15% higher first-year signing bonus, for each year with the college team. On average, a rookie is estimated to earn 131,000 more in his rookie season, if he enters the NFL one year later. Our analysis of a typical labor market in professional sports shows that the returns to ed- ucation in sports are sizeable and surprisingly similar to returns to formal education. The results of our analysis provide information for the players who are deciding about declaring for the draft, however, also colleges and the teams in the NFL may find the results of interest.
Keywords: J31; 330; NFL; returns to education; ability bias; labor markets in sports; Fußballsport; Professioneller Sport; Bildungsertrag; Schätzung; USA